A methodology for assessing basis risk ‐ Abstract of the London Discussion. (2nd September 2015) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> This abstract relates to the following paper: IFoA/LLMA (2014) Longevity Basis Risk. A methodology for assessing basis risk by Cass Business School and Hymans Robertson LLP. Available at http://www.actuaries.org.uk/sites/all/files/IFoA%20LLMA%20Longevity%20Basis%20Risk%20Report_0.pdf